2010
DOI: 10.3163/1536-5050.98.4.005
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the literature of health education: 2006–2008

Abstract: The results of this study provide a new picture of the health education literature: The volume has grown significantly, cites older materials, and relies less on sexual health journals and more on psychology journals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 4 publications
0
11
0
2
Order By: Relevance
“…Strothmann's results indicate that, in addition to Social Work journals, a list of core Social Work journals should also include specific journal titles in psychiatry, psychology, medicine, and law. 17 On the other hand, working with citations from the History of Technology, Katherine McCain reports that 65 percent of citations are to books and 35 percent are to serials. 9 For instance, the Nation and the New York Times both are cited by more than 44 percent of the scholars studied by Weissinger. In addition, some studies use citation analysis to assess the interdisciplinary or cross-disciplinary nature of a particular social sciences field, with the aim of informing collection development, library instruction, and the acquisition of indexing tools.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Strothmann's results indicate that, in addition to Social Work journals, a list of core Social Work journals should also include specific journal titles in psychiatry, psychology, medicine, and law. 17 On the other hand, working with citations from the History of Technology, Katherine McCain reports that 65 percent of citations are to books and 35 percent are to serials. 9 For instance, the Nation and the New York Times both are cited by more than 44 percent of the scholars studied by Weissinger. In addition, some studies use citation analysis to assess the interdisciplinary or cross-disciplinary nature of a particular social sciences field, with the aim of informing collection development, library instruction, and the acquisition of indexing tools.…”
Section: Literature Reviewmentioning
confidence: 99%
“…CINAHL has improved coverage of the core journals of physical therapy, especially for those in Zone 1. However, when looking at the coverage for Zones 1 and 2 in the current study, Scopus provided the strongest cover- [20], in an update of the mapping of the health education literature, found that percentages of journals in the core (Zones 1 and 2) remained stable. The present study, likewise, was comparable with the percentage in each zone in the Wakiji study [10].…”
Section: Discussionmentioning
confidence: 52%
“…As noted by Potter [20], updates of previous bibliometric studies give a ''fresh snapshot, a redrawn map'' for a discipline's literature. In journal publications in the field of physical therapy, journals were cited (83% of citations) more frequently than books or other types of documents.…”
Section: Resultsmentioning
confidence: 99%
“…In previous studies that mapped the literature of public health, journal articles were cited around 60%-75% of the time, with books, government documents, and miscellaneous items cited less often but still relatively frequently [13,[26][27][28][29]. The only similar ratio of cited publication types in public health disciplines is in environmental health, where 85.5% of citations were to journal articles [30].…”
Section: Discussionmentioning
confidence: 99%